Kan en diakonal organisasjon være «livssynsåpen»? (Tidsskrift for Praktisk Teologi, 2025)
Several Christian NGO and faith-based institutions have taken up the vocabulary of the Government blue paper, The word view affirmative society (2013). This is also the case for Kirkens Bymisjon. The organisation has produced the pamphlet “world-view affirmative diaconia”. The article argues that this use of world-view affirmation raised several problems for the organization, especially when it comes to the analogy between the state and Kirkens Bymisjon. The article ends by asking if there are a more appropriate use of the term. It discusses if employing religious leaders from non-Christian denominations may be a more appropriate operationalization of how a faith-based organisation may be “world-view open” (livssynsåpenhet).
Keywords: Diakoni; Kirkens bymisjon; livssynsåpenhet; religionsmangfold